2021
DOI: 10.3390/infrastructures6090118
|View full text |Cite
|
Sign up to set email alerts
|

The Main Impacts of Infrastructure Works on Public Roads

Abstract: Infrastructure implementation and renovation in cities require work on public roads that impact the daily lives of road users and local population and commerce. Although the study of the impacts of infrastructure works in the researched literature has received various approaches, there is still a shortage of studies that identify the impacts of the implementation of infrastructure on public roads and the importance of each one. This study collaborates with this theme by researching the main impacts caused by i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…On the other hand, there is a negative impact from the existence of infrastructure development projects that trigger social conficts as the fndings of Khanani et al [2] explain the negative impact of road infrastructure development in the form of shifting the places of the poor to the interior which also changes the social pattern of the region that has been well organized, and also it is detrimental to the poor who live in the area of road infrastructure development and to the spatial impact of changes in agricultural land. Tis negative impact is also reinforced by survey research by Santos et al [5] who explain the existence of public rejection on the basis of environmental impacts in the form of a decrease in air quality during infrastructure development. Several previous studies generally show that there are pros and cons related to the impact of infrastructure development, or in other words, there is no visible mitigation efort to prevent negative impacts so as to balance the impact of infrastructure development on the community.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…On the other hand, there is a negative impact from the existence of infrastructure development projects that trigger social conficts as the fndings of Khanani et al [2] explain the negative impact of road infrastructure development in the form of shifting the places of the poor to the interior which also changes the social pattern of the region that has been well organized, and also it is detrimental to the poor who live in the area of road infrastructure development and to the spatial impact of changes in agricultural land. Tis negative impact is also reinforced by survey research by Santos et al [5] who explain the existence of public rejection on the basis of environmental impacts in the form of a decrease in air quality during infrastructure development. Several previous studies generally show that there are pros and cons related to the impact of infrastructure development, or in other words, there is no visible mitigation efort to prevent negative impacts so as to balance the impact of infrastructure development on the community.…”
Section: Introductionmentioning
confidence: 91%
“…Several studies have basically shown that road infrastructure development creates various positive and negative impacts on the socioeconomic sphere [1][2][3], to impacts on development. Sustainability and the environment [4][5][6]. In the socioeconomic context, Gibbons et al [1] explain that the economic impact lies in the benefts of the road network built on local labor productivity variables and wages when using transportation access patterns and achieving time efciency.…”
Section: Introductionmentioning
confidence: 99%
“…Sustainable embankment materials are desired globally by geotechnical experts from durability, cost-efectiveness, and optimization perspectives for civil engineering infrastructures [1][2][3][4][5][6][7][8][9][10]. Urbanization around the world is going on fast-track [11] due to which the problematic soils sites are also in demand for soils improvement (stabilization).…”
Section: Introductionmentioning
confidence: 99%